Reviews and notices - Gustawsson, Elisabeth; Cronquist, Ulf; Bowen, Rhonwen; Danatus, Ulf; Eriksson, Andreas; Olofsson, Arne; Lindblad, Per; Modiano, Marko; Stålhammar, Mall; Westphal, Bärbel; Pankow, Christiane; Forssell, Louise (Moderna Språk, 2005)
Includes the following reviews: p. 219. Elisabeth Gustawsson. Svartvik, J., & Svartvik, R., Sagt och gjort: engelska idiom, ordspråk, talesätt, citat. p. 219-221. Ulf Cronquist. Bortolussi, M. & Dixon, P., Psychonarratolofy. Foundations for the Empirical Study of Literary Response. p. 221-222. Rhonwen Bowen. Swan, M., Practical English Usage. p. 222-224. Ulf Danatus. McKinney, D., Magic Circles: The Beatles in Dream and History. p. 224-225. Andreas Eriksson. Ellis, R. & Barkhuizen, G. Analysing Lerner Language. p. 226-229. Arne Olofsson. Huddelston, R. & Pullum, G. K., A Student's Introduction to English Grammar. p. 229-231. Per Lindblad. Ashby, M. & Maidment, J., Introducing Phonetic Science. p. 231-233. Marko Modiano. Jenkins, J., World Englishes: A Resource Book for Students. p. 233-234. Mall Stålhammar. Koch, H. & Kjaer, A. L., Europeisk retskultur - på dansk. p. 234-236. Bärbel Westphal. Schnaas, U., Das Phantastische als Erzählstrategie in vier zeitgenössischen Romanen. p. 236-239. Christiane Pankow. Hentschel, E. & Weydt, H., Handbuch der deutsche Grammatik. p. 239-240. Louise Forssell. Anonyma., Eine Frau in Berlin. Tagebuchaufzeichnungen vom 20. April bis 22. Juni 1945. Mit einem Nachwort von Kurt W. Marek.